2017
DOI: 10.1177/1460408617711729
|View full text |Cite
|
Sign up to set email alerts
|

In-situ simulation

Abstract: In-situ' simulation or simulation 'in the original place' is gaining popularity as an educational modality. This article discusses the advantages and disadvantages of performing simulation in the clinical workplace drawing on the authors' experience, particularly for trauma teams and medical emergency teams. 'In-situ' simulation is a valuable tool for testing new guidelines and assessing for latent errors in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Due to our unit’s high bed occupancy rate, access to an actual bed space to conduct the scenarios was problematic. As such, we felt that resorting to an adapted teaching room (within the intensive care unit) did not provide a realistic enough environment, detracting the programme from the main advantage of in situ simulation 5. Interestingly, anecdotal feedback from participants attending both settings reported that the scenarios felt more real in the simulation centre.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Due to our unit’s high bed occupancy rate, access to an actual bed space to conduct the scenarios was problematic. As such, we felt that resorting to an adapted teaching room (within the intensive care unit) did not provide a realistic enough environment, detracting the programme from the main advantage of in situ simulation 5. Interestingly, anecdotal feedback from participants attending both settings reported that the scenarios felt more real in the simulation centre.…”
Section: Methodsmentioning
confidence: 98%
“…Despite the growing popularity of in situ simulation,5 and in contrast to the previous programme, we decided to deliver the training in the purpose-built simulation centre within the Trust. Due to our unit’s high bed occupancy rate, access to an actual bed space to conduct the scenarios was problematic.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] The scenarios for the ISS were carefully selected to cover the range of maternal, obstetrics and neonatal emergencies in various combinations, to test and stress the workflow and micro-systems in place. These insitu simulation scenarios, usually commenced in the ED resuscitation room and will follow through into the labour ward, admitting ward or the emergency operating theatre, as appropriate [7,8]. Some examples of the scenarios include, maternal cardiac arrest, premature labour, breech deliver, cord prolapse and eclamptic seizures.…”
Section: Introductionmentioning
confidence: 99%